Expression and NMR Structural Studies of Isotopically Labeled Cannabinoid Receptor Type II - Yeliseev, Alexei (Methods Enzymol, 2017)
Cannabinoid receptor type II (CB(2)) is an integral membrane protein with seven transmembrane helices that belongs to the large superfamily of rhodopsin-like G protein-coupled receptors (GPCR). The CB(2) is part of the endocannabinoid system that plays a vital role in regulation of immune response, inflammation, pain, and metabolic processes. Information about the structure and function of CB(2) in cell membranes is essential for development of specific pharmaceuticals that target CB(2) signaling. Methodology for recombinant expression, stable isotope labeling, purification, reconstitution into liposomes, and NMR characterization of functionally active CB(2) is presented. Uniformly (13)C, (15)N-labeled CB(2) protein is expressed by fermentation of E. coli in a medium of defined composition under controlled aeration, pH and temperature and purified by tandem affinity chromatography. The receptor reconstituted into lipid bilayers is suitable for structural studies by solid-state NMR spectroscopy at low temperature.